Support to SMEs - Increasing research and innovation in SMEs and SME development. Work package 2. Saxony (DE): Regional Operational Programme ERDF 2007-2013. Case Study - Christian Köhler; Michaela Niefert (European Commission, 2015)
The objective of this study is to perform an ex-post evaluation of the instruments applied in the OP ERDF Saxony 2007-2013 to facilitate SMEs' growth and innovation. The analysis encompasses 9 instruments that were identified as either targeting SMEs in particular or being mainly absorbed by SMEs. Applying the theory-based impact evaluation, the study firstly examines the intervention logic of the OP and also to what extent the applied instruments are appropriate in order to achieve the declared objectives. Secondly, evidence of achievements is presented providing an in-depth understanding of the mechanisms and conditions influencing the instruments impact on SMEs' growth and innovation. Data collection included publicly available hard data, information provided by strategic and programming documents, annual implementation reports, evaluation studies, and indicators from the monitoring system complemented by a number of telephone interviews with representatives of the managing authority, awarding authority, beneficiaries, stakeholders and individual experts. Data collection was carried out during the period November 2014 - May 2015.
Keywords: 330; SMEs; Enterprise Success; EU Structural Funds; EU SME Research; Saxony; KMU; Unternehmenserfolg; Mittelstandspolitik; EU-Strukturfonds; Mittelstandsforschung; Sachsen